Love And Tragedy in Four Stories of War of The Twentieth Century: Erich Maria Remarque, Ernest Hemingway. Tristan and Iseult Revisited? - Corona Martínez, Laura (Amaltea. Revista de Mitocrítica, 2018)
The influence of the Western imaginary of tragic love, from Tristan and Iseult to our days, appears in the different declinations of the myth, from love-passion or amour fou to the popular accents of melodrama, with its repetitive logic of the obstacles. A use of the fatality inscribed in the archetypal amorous plot seems to potentiate, in an unexpected way, the capacity of denunciation of certain celebrated novels of the twentieth century on the subject of the war. Such connotations could shed light on the importance of the confrontational dimension between individual and society contained in the original legend.